(untitled) (International Journal of Medical and Surgical Sciences, 2018)
Dental caries is a multifactorial, infectious and communicable disease, and Streptococcus mutans is the key microorganism related to this pathology. The objective of this study was to evaluate the association between the levels of Streptococcus mutans and caries in schoolchildren. Descriptive, cross-sectional study conducted on 100 schoolchildren aged 6 to 10 years from the Unidad Educativa Checa Cuenca, Ecuador. ICDAS index and odontogram were used to measure the prevalence and severity of caries. For the identification and quantification of Streptococcus mutans , dental plaque samples were used for cultivation and biochemical tests (MicroScan). The results were analyzed statistically using absolute and relative frequencies, for bivariate analysis Chi-squared test and Fisher’s Test ( p <0.05) were used. 96% of the schoolchildren presented dental caries, 69% of them were children aged 8 to 10 years, the prevalence of caries was higher in females reaching 57%. High (60,000UFC/ml) and very high (70,000UFC/ml) levels of Streptococcus mutans were found on schoolchildren aged 8 to 10 years reaching 22% and 8%, respectively ( p =0.005). Regarding sex, high (60,000UFC/ml) as well as very low (0- 20,000UFC/ml) levels of Streptococcus mutans appeared without difference by sex ( p = 0.355). Schoolchildren without caries presented a low count of Streptococcus mutans (0 -20,000 UFC/ml), children with caries presented variable levels of Streptococcus mutans , although higher than 20,000UFC/ml ( p <0.001). Conclusion: there is a high prevalence of caries in the school population with high levels of Streptococcus mutans.